Modification of Calcium Oxide Catalyst Derived from Chicken Eggshell Waste with Magnesium Oxide to Enhance Biodiesel Synthesis from Crude Palm Oil - Hamidah, Fikriyah; Septaningsih, Dewi Anggraini; Fahri, Mirad; Basuki, Rahmat; Gunaryo; Subiakto, Amadea Kenyoning Hapsari; Nismarawati, Ardine Kusuma; Ningrum, Hanifa Setya; Fajry, Zaydan Al; Erwinda, Maura Agnes; Afandi, Achmad Kusyairi (Indonesian Scholar Society, 2025)
Biodiesel is a promising renewable energy source to replace conventional diesel fuel. This study aims to improve biodiesel production efficiency by utilizing a heterogeneous catalyst derived from chicken eggshell-based calcium oxide (CaO), modified with magnesium oxide (MgO). The catalyst was synthesized via co-precipitation and applied in both transesterification and interesterification reactions using crude palm oil (CPO) as feedstock. The optimum reaction was conducted at 65°C for 180 minutes with a 9:1 methyl acetate/methanol to oil molar ratio and 2.5 wt% catalyst loading. The modified CaO.MgO catalyst outperformed unmodified CaO, yielding 89.63% and 99.96% biodiesel via interesterification and transesterification, respectively. The catalyst characterization was performed using FTIR, XRD, and GC-MS, confirming the enhancement in basicity, crystallinity, and FAME content. This study demonstrates the potential of waste-derived catalysts in sustainable biodiesel production while addressing environmental waste issues.